SISTEM INFORMASI PREDIKSI PENJUALAN ALAT TULIS KANTOR DENGAN METODE FP-GROWTH (STUDI KASUS TOKO KOPERASI SEKOLAH BINA MULIA) - Srisulistiowati, Dwi Budi; Khaerudin, Muhamad; Rejeki, Sri (Universitas Dirgantara Marsekal Suryadarma, 2021)
AbstractThe increase in sales transactions accompanied by the availability of goods sold is a reflection of the performance of a company's business (store). One of the business units in Bina Mulia School is a shop that sells a variety of office stationery equipment. Therefore, a computerized system is needed in order to solve all problems in the company and be able to ease the task of employees in analyzing and taking into account the inclusion and sale of office stationery for the future. So it is necessary to design a Data Mining Warehouse system for decision makers in determining policies quickly, efficiently, and effectively. One of the data mining warehouse methods is FP-Growth. The FP-Growth algorithm is used to determine which data sets appear most frequently in a data set. The method in frequent itemsset search using FP-Growth algorithm works very well in performing Frequent itemsset by generating rule from ATK sales data. In implementing the FP-Growth algorithm in the atk inventory prediction application can be seen from the number of items sold and to know the number of frequent itemset that occur. FP-Growth algorithm can be applied to support ATK sales strategy in Bina Mulia School Cooperative so that management can make decisions quickly.Â Keywords : Sales, Precipitation, FP Growth, ATK